Efektifitas Penggunaan Analisis Teknikal Stochastic Oscillator dan Moving Average Convergence-Divergence (MACD) pada Perdagangan Saham-Saham Jakarta Islamic Index (JII) di Bursa Efek Indonesia - Adi Prabhata (Sinergi: Kajian Bisnis dan Manajemen, 2012)
The study was conducted to measure the effectiveness of using two tools of technical analysis, namely the Stochastic Oscillator and Moving Average Convergence Divergence (MACD) in 10 stocks of the Jakarta Islamic Index (JII) in Indonesia Stock Exchange within three years, 2008, 2009, and of 2010. The conclusions are that in that year, the use of the Stochastic Oscillator generates signals true on average for every 47.1 times as many shares or 72.76% and false signals as much as 18.3 times, or 27.24%. The use of true MACD signal produced 14.10 times (61.81%), false signal 8.7 times (38.19%). These results indicate that the use of technical analysis tools that can provide a return on stocks JII. It was not statistically proven that the Stochastic Oscillator gives better results than the MACD, or vice versa. Furthermore, although these tools provide benefits, but not proven that these tools can provide abnormal returns for its users. This study also implies that the capital market in Indonesia, especially stocks that meet the criteria of Islamic stock market does not show any efficiency.Keywords: Jakarta Islamic Index (JII), Analisis teknikal, Stochastic Oscillator, Moving Average Convergence-Divergence (MACD).